Long‐term results of a prospective, single‐arm evaluation of everolimus‐eluting bioresorbable vascular scaffolds in infrapopliteal arteries. Issue 1 (10th October 2020) - Varcoe, Ramon L.; Menting, Theo P.; Thomas, Shannon D.; Lennox, Andrew F.
Abstract: Objectives: The aim of this study was to perform a long‐term evaluation of an everolimus eluting, bioresorbable vascular scaffold (BVS) in the treatment of de novo atherosclerotic disease within crural arteries. Methods: A prospective, single‐arm study was performed enrolling patients with chronic lower limb ischemia between 2013 and 2018. Results: Fifty‐five limbs in 48 patients (56% male; mean age 82.1 ± 8.0 years, range 65–97) were treated for critical limb ischemia (72.7%) or severe claudication (27.3%). Seventy‐one scaffolds were used to treat 61 lesions with a mean length of 20.1 ± 10.8 mm. During a mean follow‐up period of 35.2 ± 20.4 months, 22 (45.8%) patients had died. No late or very‐late scaffold thrombosis was observed. Overall, clinical improvement was observed in 90.9% and a limb‐salvage rate of 100% was observed. Binary restenosis was detected in 11/71(15.5%) scaffolds. Primary patency and freedom from clinically driven target lesion revascularization rates at 12, 24, 36, 48, and 60 months were 90.8% (95% confidence interval 80.7–95.8), 90.8% (80.7–95.8), 79.7% (65.8–88.4), 76.3% (61.1–86.2), 72.3% (55.5–83.4) and 97.2% (89.2–99.3), 97.2% (89.2–99.3), 90.7% (78.7–96.1), 90.7% (78.7–96.1), and 90.7% (78.7–96.1), respectively. Conclusions: This long‐term study shows excellent rates of patency and freedom from target lesion revascularization using the absorb BVS below‐the‐knee. This proof of concept study lays the foundation for the next generation of BVS to be evaluated in infrapopliteal arteries.